2015
DOI: 10.1111/josh.12235
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Playworks on Boys' and Girls' Physical Activity During Recess

Abstract: The current findings suggest that Playworks had a significant impact on some measures of girls' physical activity, but no significant impact on measures of boys' physical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 29 publications
2
20
1
1
Order By: Relevance
“…However, these results do contribute to the literature the idea that a structured program may not always be the best practice for each school or school district. These results contradict another study published about a structured PA program that stated the approach was successful in improving girls' PA but not boys' PA …”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, these results do contribute to the literature the idea that a structured program may not always be the best practice for each school or school district. These results contradict another study published about a structured PA program that stated the approach was successful in improving girls' PA but not boys' PA …”
Section: Discussioncontrasting
confidence: 99%
“…These results indicate that a structured approach may not always be effective in increasing PA. This contradicts another study regarding a structured PA program that found that the program was effective in increasing girls' PA, but not boys' PA . To our knowledge, little past research exists regarding the effects of structured programs on students' PA.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…However, the SB level of boys and girls was similar and the increasing trends were also similar for both genders. A previous study reported that SB was easier for girls to control but this was not the case for boys [56]. The study indicated that if girls and boys had the same SB levels, more attention should be focused on boys since overweight and obese male adults are more likely to suffer poor cardiovascular health compared with their female counterparts.…”
Section: Discussionmentioning
confidence: 96%
“…These changes should result in positive increases in GRF-OT items related to boundaries, availability of equipment, games, and participation in active play. Results from previous randomized controlled trials have shown higher levels of physical activity for girls [8] and minority students [9]. The Playworks program also provides student leadership opportunities through a Junior Coach leadership program where students are recruited and trained to become leaders amongst their peers.…”
Section: Introductionmentioning
confidence: 99%